Pyogenic Granuloma: An Unusual Cause of Massive Gastrointestinal Bleeding from the Small Bowel - Dana C Moffatt; Paul Warwryko; Harminder Singh (Canadian Journal of Gastroenterology)
Small bowel hemorrhage is responsible for approximately 4% of all cases of gastrointestinal bleeding. The etiology of bleeding from the small bowel is a tumour in approximately 10% of cases. Pyogenic granuloma is a common inflammatory vascular tumour of the dermis, which rarely occurs in the gastrointestinal tract. Pyogenic granuloma is a rare cause of overt or obscure small bowel bleeding. The present paper reports the first case of pyogenic granuloma presenting as a massive gastrointestinal bleed, and reviews the relevant literature to date regarding the clinical presentation, diagnosis and management of this rare gastrointestinal lesion.